Reflective Analysis of PGSD Students' Science Process Skills in the Perspective of 21st Century Skills - Maria Melani Ika Susanti (Jurnal Penelitian Pendidikan IPA, 2025)
The rapid shift toward 21st-century learning requires prospective primary teachers to master science process skills (SPS) that support critical thinking, problem-solving, and innovation. This study aims to analyse PGSD students’ SPS and 21st-century skills through a reflective approach. A descriptive qualitative design supported by quantitative data was employed. Data were collected from 22 first-year PGSD students enrolled in an elementary science education course using a Likert-scale questionnaire and written reflective journals. Questionnaire data were analysed descriptively using mean scores and categorical achievement levels, while journal data were examined through thematic analysis. The results show that students’ SPS are at a very high level (M = 4.21), particularly in observing, conducting experiments, drawing conclusions, and applying scientific concepts. Their 21st-century skills are at a high level (M = 4.19), with collaboration and critical thinking higher than creativity and communication. Reflective journals confirm that practice-based and project-based science activities help students recognise their strengths and weaknesses and plan improvements. It can be concluded that reflective, experiment-oriented science learning effectively develops SPS and 21st-century skills in prospective primary teachers, although communication and creativity still need systematic reinforcement